Avaliação do eco glandular endocervical como marcador ultrassonográfico na predição do parto prematuro espontâneo - Oliveira, Gustavo Henrique de (2010)
Aim: To evaluate the importance of cervical gland area (CGA) to predict spontaneous preterm birth (SPB). Method: A prospective study was performed from October 2008 to September 2009 of 102 singleton pregnancies at 20 and 24 weeks. A transvaginal ultrasound during the routine morphological scan investigated: the cervical length, CGA, its thickness and signs of cervical funneling. A preterm birth is defined as one that occurs at less than 37 weeks gestation. Ultrasound and clinical variables were submitted to univariate analysis by calculations of descriptive statistics, the Student t-test, percentages, and two-dimensional associative arrays evaluated using the Fisher exact test and odds ratio. The level of significance was set at 5%. Results: Of the 102 patients, four were lost in the follow up and seven were excluded as delivery was induced prematurely; ten patients presented spontaneous preterm births and 81 at term. The mean maternal age was 28.8 years old (18-41 years) without significant difference between the spontaneous preterm birth and term groups. There were statistical differences in the mean (33.9 vs. 36.1 cm), median (33.5 vs. 37.0 cm) and spread (standard deviation: 9.6 vs. 7.0) of the cervical length between the two groups. Risk factors for SPB gave an odds ratio of 15.06. All patients presented a CGA with a mean thickness of 8.4 mm (5.1 to 15 mm – SD: 3.1) for SPB and 8.9 mm (3.0 to 13.9 mm – SD: 2.3) for term individuals. Conclusion: The results suggest that the presence or absence and thickness of CGA are not correlated to SPB even in clinically or ultrasonographically high-risk patients. Further studies are necessary to reevaluate the parameters used to predict SPB.